Highly Efficient Hydrogen Evolution from a Mesoporous Hybrid of Nickel Phosphide Nanoparticles Anchored on Cobalt Phosphosulfide/Phosphide Nanosheet Arrays. Issue 6 (13th January 2019) - Sun, Jingying; Ren, Muqing; Yu, Luo; Yang, Ze; Xie, Lixin; Tian, Fei; Yu, Ying; Ren, Zhifeng; Chen, Shuo; Zhou, Haiqing
Abstract: Facile design of low‐cost and high‐efficiency catalysts with earth‐abundant and cheap materials is desirable to replace platinum (Pt) for the hydrogen evolution reaction (HER) in water splitting, but the development of such HER catalysts with Pt‐like activity using simple strategies remains challenging. A mesoporous hybrid catalyst of nickel phosphides nanoparticles and cobalt phosphosulfide/phosphide (CoS|Ni|P) nanosheet arrays for HER is reported here, which is developed by a facile three‐step approach consisting of electrodeposition, thermal sulfurization, and phosphorization. This hybrid catalyst is highly robust and stable in acid for HER, and is distinguished by very low overpotentials of 41, 88, and 150 mV to achieve 10, 100, and 1000 mA cm −2, respectively, as well as a small Tafel slope (45.2 mV dec −1 ), and a large exchange current density (964 µA cm −2 ). It is among the most efficient earth‐abundant catalysts reported thus far for HER. More importantly, this electrocatalyst has electrochemical durability over 20 h under a wide range of current densities (up to 1 A cm −2 ) in acidic conditions, as well as very high turnover frequencies of 0.40 and 1.26 H2 s −1 at overpotentials of 75 and 100 mV, respectively, showing that it has great potential for practical applications in large‐scale water electrolysis. Abstract : A highly active and durable hydrogen‐evolving electrocatalyst, which requires a very low overpotential of 41 mV to achieve 10 mA cm −2, and has a very large turnover frequency of 1.26 H2 s −1 at 100 mV overpotential, is developed by in situ growing nickel phosphide nanoparticles on 3D cobalt phosphosulfide/phosphide nanosheet arrays.